The Application of the Principles of Transparency, Accountability, and the Concept of the Value of Money in the Financial Management of the Pujimulio Sunggal Village Government - Nazwa Sabina Nasution; Nur Ahmadi Bi Rahmani; Annio Indah Lestari Nasution (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the implementation of the principles of transparency, accountability, and Value for Money in the financial management of the Pujimulyo Village Government, Sunggal Subdistrict. Effective village financial governance is essential to ensure responsible public administration, strengthen public trust, and optimize the utilization of public resources for community welfare. This research employed a descriptive-analytical method with a predominantly qualitative approach, supported by quantitative budget data analysis. Secondary data were collected from the Village Revenue and Expenditure Budget (APBDes), the Village Government Work Plan (RKPDes), and publicly available financial documents for the 2024–2025 fiscal years. The analysis was conducted by first calculating the Value for Money ratios (economy, efficiency, and effectiveness) and subsequently interpreting the results qualitatively to evaluate the implementation of transparency, accountability, and governance practices in village financial management. The findings indicate that the economic and efficiency ratios improved from 103.98% in 2024 to 92.22% in 2025, reflecting better budget control and resource utilization. The effectiveness ratio remained stable at 90%, indicating that most development programs were implemented according to plan. Although transparency has been demonstrated through the publication of village financial infographics and accountability has generally been reflected in the implementation of planned programs, the completeness of financial information and the quality of performance reporting still require improvement. Overall, the study concludes that the principles of transparency, accountability, and Value for Money have been implemented reasonably well in the financial management of Pujimulyo Village, although further improvements are needed to strengthen governance quality and maximize public value.